Freezing of Gait in Multiple System Atrophy - Yang, Huaguang; Liu, Weiyin Vivian; Wang, Shanshan; Yang, Wenbin; Liu, Changsheng; Wen, Zhi; Hu, Lanhua; Guo, Jinxia; Fan, Guoguang; Luo, Xiaoguang; Zha, Yunfei (Frontiers in Aging Neuroscience, 2022)
Background and Purpose: Freezing of gait (FOG) is a common gait disturbance phenomenon in multiple system atrophy (MSA) patients. We investigated the incidence and clinical correlations of FOG in this cross-sectional clinical study. Methods: A total of 99 MSA patients were consecutively enrolled in this study from three hospital centers in China. Eight patients were excluded in the analysis due to incomplete information. We discovered the prevalence of FOG symptoms in the MSA cohort, and assessed the clinical factors of MSA patients with and without FOG. Results: Of 91 MSA patients, 60 (65.93%) showed FOG. The incidence increased with disease duration and motor severity and was correlated with modified Hoehn and Yahr (H-Y) stages [odds ratio (OR), 0.537; 95% confidence interval (CI), 0.313–3.920], longer disease duration (OR, 0.538; 95% CI, 0.370–0.782), higher Unified Multiple System Atrophy Rating Scale (UMSARS) score (OR, 0.963; 95% CI, 0.932–0.994), MSA-cerebellum subtype (OR, 2.988; 95% CI, 1.218–7.328), levodopa-equivalent dose (LDED) (OR, 0.998; 95% CI, 0.997–1.000), and higher Scale for the Assessment and Rating of Ataxia (SARA) score (OR, 0.801; 95% CI, 0.724–0.885) (logistic regression). Motor dysfunction was significantly positively related to lower quality of life scores (P < 0.01). Conclusion: FOG is a common symptom in MSA patients and correlated with poor quality of life, disease progress and severity, LDED, and cerebellum impairment.